Evaluation of the Low Inclusion of Full-Fatted Hermetia illucens Larvae Meal for Layer Chickens: Growth Performance, Nutrient Digestibility, and Gut Health - Chu, Xiaohua; Li, Mengmeng; Wang, Guiying; Wang, Kuiming; Shang, Rongsheng; Wang, Ziyu; Li, Lusheng (Frontiers in Veterinary Science, 2020)
Substitution of feed protein source with defatted black soldier fly larvae meal (BSFM) has been evaluated intensively in poultry. But the information about full-fatted BSFM is still very limited. The aim of the present study was to investigate effect of dietary low inclusion of full-fatted BSFM on growth performance, plasma antioxidant ability, nutrient digestibility, and gut health of layer chickens during 1-42 d of age. A total of 480 female 1-d old Hy-Line Brown chickens were divided into four dietary treatments with the inclusion of 0%, 3%, 6%, and 9% of full-fatted BSFM. Each treatment included 6 replicates and 20 birds per replicate. As dietary full-fatted BSFM inclusion levels increased, there was a quadratic increase in final weight and ADG and a quadratic decrease in F/G. Dietary full-fatted BSFM inclusion levels increased the digestibility of CP and EE quadratically as well as ileum mucosal sIgA concentration linearly, but had no effect on intestinal morphology. Additionally, an increase in dietary full-fatted BSFM inclusion levels resulted in a linear increase in GSH-Px and T-SOD activities and a linear decrease in MDA content in plasma. The encouraging results of the improvement of growth performance, nutrient digestibility, antioxidant ability, and gut health parameters suggested that partially full-fatted BSFM inclusion can be suitable protein ingredients for layer chickens diets at the started period.